Answer: --42
Step-by-step explanation:
All that you have to do in this equation is substitute the value of x given with the x's in the expression. SO...
Expression: -4(5x+2) - 6(x-3)
Substitute: -4(5(2)+2) - 6((2)-3)
Solve: -4(10+2) - 6(-1)
-4(12) - 6(-1)
-48 +6
Answer: -42
Hope this helps!
Answer:
Step-by-step explanation:
1. 6x + 12 = 3x - 27
3x + 12 = -27
3x = -39
x = -13
2. 2p - 3 = 3p + 2
-p - 3 = 2
-p = 5
p = -5
3. 6x - 2 - 35x -28 = 18x - 27
-29x - 30 = 18x - 27
-47x - 30 = -27
-47x = 3
x = -3/47
Answer:
somewhere between them i think
Step-by-step explanation: